Hubungan Pengetahuan Pengguna Lensa Kontak dengan Kejadian Dry Eyes - Husna, Hanna Nurul; Ibrahim, Riza Ahmad; Witjaksono, Arief (Jurnal Kesehatan Holistic, 2021)
Contact lenses are used for therapeutic and cosmetic purposes. One of the eyes complications that often occur from contact lens users’ is dry eyes. The aim of this study was to determined relationship between knowledge and dry eyes in contact lens users. The quantitative research method was used in this study. The data was analyzed descriptively and the hypothesis testing was tested using the chi-square test. 46 students were involved in this study, using questionnaire and the Schimer test to collect the data. The result showed that knowledge level of wearing contact lens was categorized as good; knowledge level of the length of contact lens wearing was categorized as good; and knowledge level of contact lens storage was categorized as good. The contact lens users; complaint that often report was felt like a foreign thing enter into the eyes (41.3%). With an objective assessment using Schimer test, there were seven right eyes (15.25) and six left eyes (13 %) had dry eyes. There is no relationship between knowledge of contact lens users and the incidence of dry eyes.